Planning of strategies to improve the learning of multiplication and division - María teresa Guerrero Fernández, Emiro Enrique Méndez Mulett, (Universidad Pedagógica y Tecnológica de Colombia, 2010)
When demonstrating itself great difficulty of the learning of the multiplication and the division in students of the degree sixth of the Technical Institute Santo Tomás de Aquino de Duitama, becomes necessary to determine the causes of this problem and its possible solutions, with the hypothesis that the problem can be due to the lack of methodology or didactic strategies, it was made an investigation looking for to correct the learning problem. For it, educational ones were polled seven  of the area of mathematics  and  190 students of the degree sixth, soon the collected information was analyzed and a pedagogical proposal based on the planning, design and application of educative factories was constructed, by means of the resolution of problems, using the method of the four passages of Polya, which was applied to 48 students, being that the academic yield of them in the first period, improved respect to the previous years substantially, also the work of education to the educational ones was facilitated. This investigation welcomes the theories on learning of Piaget, Carretero, those of planning for the learning of Ander-Egg, those of learning by resolution of problems of Polya and the one of the Educative Maya Factory Betancourt.